2021
DOI: 10.48550/arxiv.2107.00457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Slowly expanding stable dust spacetimes

David Fajman,
Maximilian Ofner,
Zoe Wyatt

Abstract: We establish the future nonlinear stability of a large class of FLRW models as solutions to the Einstein-Dust system. We consider the case of a vanishing cosmological constant, which in particular implies that the expansion rate of the respective models is linear i.e. has zero acceleration. The resulting spacetimes are future globally regular. These solutions constitute the first generic class of future regular Einstein-Dust spacetimes not undergoing accelerated expansion and are thereby the slowest expanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…On the other hand, in the same problem if the cosmological constant is turned off (i.e., the vacuum energy is absent), then the perturbed solutions do come back to the background solution asymptotically [27,28]. Similar phenomena of asymptotic stability are observed in the study of [38], where the background solutions once again are simply the Milne universe that does not contain a non-zero energy density. In order to reach a definite conclusion about forming large-scale structures by non-linear perturbations of a background with non-vanishing energy density would require further analysis including radiation sources and possibly more observational inputs.…”
Section: Motivation and Overviewmentioning
confidence: 79%
See 1 more Smart Citation
“…On the other hand, in the same problem if the cosmological constant is turned off (i.e., the vacuum energy is absent), then the perturbed solutions do come back to the background solution asymptotically [27,28]. Similar phenomena of asymptotic stability are observed in the study of [38], where the background solutions once again are simply the Milne universe that does not contain a non-zero energy density. In order to reach a definite conclusion about forming large-scale structures by non-linear perturbations of a background with non-vanishing energy density would require further analysis including radiation sources and possibly more observational inputs.…”
Section: Motivation and Overviewmentioning
confidence: 79%
“…However, we do not claim that turning off the cosmological constant leads to instability but simply we are unable to reach a definite conclusion with the currently available method. It is worth pointing out that [38] proved the non-linear asymptotic stability of the Milne universe (devoid of background matter density) including a dust source (slowly expanding spacetime). In such a case, the individual dust particles travel along their respective geodesics and the sound speed vanishes.…”
Section: ∇[γ]mentioning
confidence: 98%
“…In the case of dust K = 0, [34] showed that small perturbations of the homogeneous fluid solutions are globally regular for all α > 1/2. If K ∈ (0, 1/3), work by some of the present authors showed that homogeneous fluid solutions are globally regular under irrotational perturbations for α = 1 [14]. The case α > 1 without the irrotational restriction was shown in [34].…”
mentioning
confidence: 72%
“…Following these earlier studies several additional ones have been performed addressing the stability issue on manifolds admitting negative spatial Einstein metrics (hyperbolic manifolds for the 3 + 1 dimensional case) including source terms in the case of small data. These include the Λ−vacuum (Λ > 0) [38,37], Klein-Gordon field [40,39] (with Λ = 0), dust [30], and Vlasov matter [44] cases, in particular. The stability of these special solutions incorporating several matter sources that satisfy the energy condition we prescribe for the analysis to hold true provides some 'weak' support for our conclusion.…”
Section: Stability Resultsmentioning
confidence: 99%